Detection of Dashboard in Fuzzy Image by Correction Force Snake Model - YU Shu-chun; DONG Jing-yi (Journal of Harbin University of Science and Technology)
In order to solve the problem that the accuracy of the dashboard detection in fuzzy images is not high，an improved Snake model based on the correction force is proposed. First，the Hough transform is used to determine the area of the dashboard in the fuzzy image. Secondly，the boundary area detected by Hough transform is the initial boundary of Snake algorithm. The correction force parameter is introduced to expand the control range of Snake algorithm，adjust the continuous control of energy function to the target curve，and achieve the precise location of the dashboard in the fuzzy image. The experimental results show that the improved Snake algorithm based on the correction force is nearly 20% better than the traditional Snake algorithm for the accuracy of the dashboard detection in the fuzzy image.